Numerical Methods in Multidimensional Radiative Transfer - Kanschat, Guido; Meinköhn, Erik; Rannacher, Rolf; Wehrse, Rainer (Springer Berlin Heidelberg : Imprint: Springer, 2009)
The book provides an overview of the numerical modelling of radiation fields in multidimensional geometries. It covers advances and problems in the mathematical treatment of the radiative transfer equation, a partial integro-differential equation of high dimension that describes the propagation of the radiation in various fields. Highly accurate and fast methods with sound analytical foundations are particularly emphasized. The volume should not only serve as a basis for the selection of suitable methods for actual radiative transfer problems in disciplines from astronomy and climatology to radiological diagnostics but also be a starting point for additional mathematical investigations on many still unknown aspects of the transfer equation.